Contesting Reports of Racism, Contesting the Rights to Assess. (June 2023) - Zhang, Tianhao
Analyzing a thread of online interaction, I apply conversation analysis and discursive psychology methods to explicate how experiences of racism are reported and contested by participants in interaction. The person reporting their experience of racism (the reporter) applies commonsense knowledge to assess the perpetrator's racist intent. Recipients of the report contest the reporter's rights to assess the perpetrator's intent while managing their lack of independent access to the reported encounter. In milder contestations, they cast doubt while avoiding assessing the situation themselves, which leads to negotiations over the accusation without contesting the correctness of the reporter's assessment. In aggravated contestations, recipients explicitly contest the reporter's assessment of the perpetrator, which leads to interactional breakdowns where moral culpabilities of both sides are implicated. Implications for understanding the moral difficulties involved in accusing racism, the interactional contingencies involved in responding to and contesting such accusations, and members' understandings of racism are discussed.